THE ROLE OF UZBEK FOLK TALES IN PROMOTING PATRIOTISM AND FRIENDSHIP EDUCATION: A COMPARATIVE ANALYSIS - Ergasheva Durdona Safarali kizi (Galaxy International Interdisciplinary Research Journal, 2023)
This scientific article that explores the significance of Uzbek folk tales in fostering patriotism and friendship education among elementary school students. The study employs a comparative analysis approach to examine the unique advantages and challenges associated with using Uzbek folk tales compared to other educational resources. The comparative analysis sheds light on the strengths of Uzbek folk tales in promoting emotional engagement and cultural relevance among students, surpassing other educational resources in these aspects. However, the study also highlights the need for adaptation and integration of folk tales into the curriculum to ensure alignment with educational frameworks.